Physiological changes modulated by rootstocks in atemoya (Annona x atemoya Mabb.): gas exchange, growth and ion concentration - Baron, D. [UNESP]; Amaro, A. C.E. [UNESP]; Macedo, A. C. [UNESP]; Boaro, C. S.F. [UNESP]; Ferreira, G. [UNESP] (Springer Nature, 2018)
Incompatibility reactions of grafted plants are triggered at the moment of grafting and/or at the early stages of re-establishment vascular connections plants; moreover, incompatibility may occur after years in orchard. The objective of this study was to evaluate the gas exchange, growth and ion concentrations on early stage after grafting to atemoya scion (Annona x atemoya Mabb.), an interspecific hybrid between cherimoya (Annona cherimola Mill.) and sweetsop (Annona squamosa L.), commonly used in food industry and for ‘in natura’ consumption, grafted onto biribá rootstock [Annona mucosa (Bail.) H. Rainer] and Annona emarginata (Schltdl.) H. Rainer var. terra-fria and mirim rootstocks to elucidate the physiological mechanisms between grafted plants. Different types of rootstocks evaluated caused variations on scion gas exchange 60 days after grafting (DAG), and these variations reflected in changes in growth at 90 DAG, which was also influenced by differential ion accumulation for each rootstock. The biribá rootstock demonstrated an increase in net carbon assimilation related to carboxylation efficiency and transpiration; however, this rootstock did not result in increased water-use efficiency. The rootstocks exhibited differences in scion leaf ion accumulation, particularly phosphorus and potassium, in biribá and araticum-de-terra-fria, respectively. We concluded that biribá rootstocks increased gas exchange and ion concentration in the atemoya scion, which were reflected directly in the vegetative growth of the scion, indicating that the physiological changes caused by this rootstock to scion do not trigger early incompatibility.
Keywords: Annonaceae; Photosynthesis; Plant propagation; Reestablishment post-grafting